Cervical Spine Involvement in a Challenging Case of Accidental Strangulation. (June 2019) - De-Giorgio, Fabio; Grassi, Simone; Miscusi, Massimo; Ricciardi, Luca; Polli, Filippo Maria
Abstract : Abstract: Although strangulation is generally homicidal, the scientific literature reports several cases in which it is suicidal or even accidental. The former eventuality is particularly interesting because extremely atypical ligatures (such as locks of hair), complex dynamics, and uncommon findings can be involved. Only a meticulous evaluation of the body and of both direct and circumstantial evidence can help in the complex differential diagnosis that includes murder, suicide, and accident. In accidental strangulation, the number and severity of injuries depend on the magnitude of applied force. This implies that high-energy strangulation (in our case, caused by the entanglement of a scarf in an electrical generator) can produce a complex polytrauma. In this case, accidental self-strangulation caused widespread, posttraumatic subarachnoid hemorrhaging, laceration of the larynx, and fracture-dislocation of the C2/C3 vertebrae. We believe that all these events contributed to the death of the victim, but the complexity of the polytrauma and the lack of direct evidence did not allow us to determine a univocal cause-effect chain.